2013
DOI: 10.1364/oe.21.029442
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, electronically controllable transverse mode selection in a multimode fiber laser

Abstract: A novel technique for the electronically-controllable generation and switching of transverse modes within a multi-mode fiber laser oscillator is presented. Preliminary results demonstrate individual transverse mode lasing and fast switching between modes with watt-level output powers. When applied to a core-pumped Tm-doped silica fiber laser with a multimode core the fundamental mode (LP 01 ), the next higher order mode (LP 11 ), or a donut-shaped LP 11 superposition were selectively excited with power levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…8b. Consequently, CT-FBGs are considered to provide great potential for broadband fiber filters [391,392].…”
Section: Chirped and Tilted Fbg (Ct-fbg) And Long Period Fbg (Lp-fbg)...mentioning
confidence: 99%
“…8b. Consequently, CT-FBGs are considered to provide great potential for broadband fiber filters [391,392].…”
Section: Chirped and Tilted Fbg (Ct-fbg) And Long Period Fbg (Lp-fbg)...mentioning
confidence: 99%
“…In fact, there are several approaches to realizing mode adjusting/switching in fiber lasers [12] , and technically an 'optical switch' combined with mode selective components should be adopted. The mode switching/adjusting operation could either be realized by real optical components, such as acoustic-optic tunable filter (AOTF) [13] , special fiber coupler [14][15][16][17] , acoustically induced fiber grating (AIFG) [18][19][20][21] , polarization controller (PC) [22][23][24][25][26][27] , and spatial light modulator [28] , or by some physical mechanisms, such as temperature control of few-mode fiber Bragg gratings (FBGs) [29] , altering the excitation condition [30] , and injection locking [31] . However, fast mode switching between different transverse modes in fiber lasers has only been demonstrated using AOTF and AIFG.…”
Section: Introductionmentioning
confidence: 99%
“…However, fast mode switching between different transverse modes in fiber lasers has only been demonstrated using AOTF and AIFG. In 2013, Daniel et al demonstrated a 5-W-level mode switchable Tm-doped fiber laser operating around 1921 nm, where the mode switching between the LP 01 and LP 11 modes is realized by an AOTF and a few-mode fiber grating [13] . The whole system was based on a bulk configuration, and the mode switching speed reached an approximately kilohertz (kHz) level.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the fast-mode switching capability can enable the use of the optimum beam characteristics for each step of the cutting process, not just for cutting of different materials or various thicknesses [16]- [19]. In 2013, J. Daniel et al realized mode selection and switching in a multimode fiber laser oscillator by adopting a few-mode fiber Bragg grating and an acoustic-optic tunable-filter as the free-space wavelength-selective element [18]. They proved that the mode is changing at the frequency of 20 kHz but could not confirm that it was switching between LP 01 and LP 11 modes.…”
Section: Introductionmentioning
confidence: 99%